Tax Avoidance: Good Corporate Governance: (Studi Kasus Perusahaan Pertambangan Terdaftar di BEI 2015-2018) - Moh. Ubaidillah (Politeknik Ganesha Medan, 2021)
Tax is an important element for the government but it becomes a burden for companies, so companies do tax evasion legally or illegally to reduce the tax burden. The purpose of this research is to determine the influence of good corporate governance (Institutional Ownership, Independent Commissioners, Audit Committee and Audit Quality) on Tax Avoidance. Independent variables in this study are Institutional Ownership, Independent Commissioners, Audit Committee and Audit Quality, while dependent variables are tax avoidance. This research was taken from mining companies listed on the IDX in 2015-2018. The population in the corporate sector is 47 companies. The samples were studied by 10 companies selected using purposive sampling techniques so that the total samples used for 4 years became 40 samples. The analysis method used is multiple linear regression analysis with SPSS 22 tool. Partial test results showed that the independent board of commissioners had a significant negative effect on tax avoidance, institutional ownership had a significant positive effect on tax avoidance, while the audit committee and the quality of audits had no effect on tax avoidance on mining companies. The results of this study can be concluded that to suppress tax avoidance, the function of independent commissioners must be strengthened.